PENGARUH MODEL PBL MENGGUNAKAN MEDIA POP UP BOOK TERHADAP BERPIKIR REFLEKTIF SISWA PADA MATERI ORGAN PENCERNAAN MANUSIA KELAS V SD - Sa'diyah, Lailatus; Rosmiati; Triman Juniarso3; Aimmatul Aliyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Reflective Thinking Skills are important for students to have. However, in reality, learning of Social Sciences on Digestive Organs Material has not implemented Reflective Thinking skills because it is still constrained in reading and reasoning is still lacking, especially if students are faced with problems related to thinking skills. In this learning, the lecture and question and answer methods are still used so that the learning process is still centered on the teacher and students are less active. This study aims to determine how the influence of the PBL Model Using Pop Up Book media on students' Reflective Thinking skills on the material of human digestive organs of grade V students and How the Response of Students' Reflective Thinking skills after the implementation of learning. This study uses a Quantitative Descriptive research method implemented at SDN SEDATI GEDE II Sidoarjo. The data collection instruments used in this study were Pretest-Postest and Student Reflective Thinking Response Questionnaire, The results showed an average N-Gain in experimental class 1 (V-A) of 0.82 with a high category. And in experimental class 2 (V-B) an N-Gain value of 0.72 was obtained with a high category. The difference is caused by the level of student understanding, as well as student readiness in capturing learning. While the results of the Reflective Thinking Response of experimental class 1 (V-A) were 76% and class (V-B) were 67%. The conclusion of this study shows that there is an influence of Reflective Thinking using the PBL learning model. It is hoped that students will get used to solving the problems they face. This is supported by the results of the Pre-post test and the results of the Reflective Thinking Response. Thus, learning becomes more active and interesting for students.